Evaluation and implementation of an intervention to promote early presentation. (1st April 2011) - Forster, A S; Forbes, L J L; Atkins, L; Patnick, J; Sellars, S; Tucker, L; Baxter, R; Ramirez, A J
Abstract : Abstract: Introduction and aims: Older women are more likely to delay presentation in breast cancer, 1 which in turn contributes to poorer survival.2 We have developed a health professional-delivered intervention to promote early presentation in older women with breast symptoms (Promoting Early Presentation (PEP) Intervention) to be delivered when they attend for their final routine mammogram. We aimed to evaluate its efficacy in an randomized controlled trial (RCT) and adapt it for use in routine clinical practice. Methods: We randomised 867 women attending for their final round of screening on the NHS Breast Screening Programme to receive either the PEP Intervention delivered by a radiographer or usual care. We measured breast cancer awareness at baseline and 2 years post-randomisation. We are adapting and piloting the PEP Intervention to be suitable for adoption in routine practice across the NHS Breast Screening Programme. Results: In the RCT, the PEP Intervention increased the proportion breast cancer aware at 2 years compared with usual care (21% vs 6%, OR: 8.1, 95% CI: 2.7 to 25.0). We have adapted the intervention so that it can be delivered feasibly while maintaining consistent quality. Conclusions: We have demonstrated the efficacy of the PEP Intervention in an RCT. We plan to evaluate its effectiveness in routine practice by implementing it in three breast screening services, and measuring feasibility, costs and health outcomes (comparing these with health outcomes in control services). Our findings will provide the data needed to inform possible implementation across the entire NHS Breast Screening Programme.